Pemahaman tentang Taharah Haid Nifas dan Istihadah: Studi Kasus Ibu-ibu Jama’ah Muslimat Yayasan Masjid Darussalam Tropodo Sidoarjo - Agus Romdlon (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2015)
The discussion of blood in women, namely menstruation, postpartum bleeding and istihaadah, is one that is most often questioned by women. It is also one of the most difficult topics in fiqh, so many people misunderstand it. Even though it has been discussed many times, there are still many Muslim women who do not understand the rules and differences between these three bloods. Perhaps this is because the blood comes out of the same channel, but in every woman, the situation is not always the same, and the rulings and handling are different. Menstruation, postpartum bleeding and istihaadah are a necessity in a woman's life, so women should not be ignorant in this matter. It affects the validity of an act of worship because it is related to purity from hadats and impurity. This study aims to reveal the understanding of the Muslim women of the Darussalam mosque in Tropodo Sidoarjo about the three bloods for women. Namely menstrual blood, postpartum and istihadhah. How the Muslim women already know or not about the theories of fiqh that have to do with the three blood. This research is characterized by a field that takes research samples in the Muslim congregation of the Darussalam Tropodo Sidoarjo mosque foundation. The results show that the understanding of Muslim women Darussalam majority already know about things that have correlation and association with menstruation, nifas and istihadhah.